Genotypic Differences between Indonesian Accessions of Wild Cowpea (Vigna vexillata) and Related Vigna Species Based on Morpho-agronomic Traits - Agung Karuniawan; M. L. Widiastuti; T. Suganda; B. L. Visser (Buletin Plasma Nutfah, 2009)
Penelitin in bertujuan untuk menguji perbedaan genotipe berdasarkan karakter morfo-agronomi di antara aksesi ‘wild cowpea’ (Vigna vexillata) dan kerabatnya dalam genus Vigna. Penelitian dilakukan di Kebun Percobaan Fakultas Pertanian Universitas Padjadjaran Bandung di Sumedang, Jawa Barat, mulai dari Oktober 2005 sampai Maret 2006. Pengujian meliputi 16 genotipe dengan dua ulangan dalam rancangan acak kelompok. Setiap genotipe ditumbuhkan dalam satu baris tanam sepanjang 6 m. Terdapat variasi yang luas dalam karakter morfo-agronomi di antara genotipe yang diuji. Analisis keragaman menunjukkan bahwa untuk beberapa karakter, aksesi V. vexillata serupa dengan kerabatnya dalam genus Vigna. Namun, beberapa tipe V. vexillata budi daya asal Bali menunjukkan hubungan yang jauh dengan kerabat liarnya asal Afrika. AbstrakThis research examined genotypic differences in morphoagronomic traits among ‘wild cowpea’ (Vigna vexillata) accessions and related groups in the genus Vigna. The traits were observed under natural, open field conditions at the field experimental station of The Faculty of Agriculture of Padjadjaran University, West Java, Indonesia, between October 2005 and March 2006. sixteen genotypes studied were planted in two replications and arranged in randomized complete block design. The plants of each genotype were grown in a single row plot of 6 m long. Large variations in morpho-agronomic traits were observed between genotypes. Analysis of genotypic differences showed that for certain traits, the V. vexillata accessions were similar to their relatives within the genus Vigna. However, some cultivated forms of V. vexillata from Bali exhibited some distinct differences from related wild genotypes of African origin.